Optimal social insurance and health inequality - Volker Grossmann; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
This paper integrates into public economics a biologically founded, stochastic process of individual ageing. The novel approach enables us to quantitatively characterize the optimal joint design of health and retirement policy behind the veil of ignorance for today and in response to future medical progress. Calibrating our model to Germany, we find that future progress in medical technology calls for a potentially drastic increase in health spending that typically should be accompanied by a lower pension savings rate and a higher retirement age. Interestingly, medical progress and higher health spending are in conflict with the goal to reduce health inequality.
Keywords: H50; I10; C60; 330; ageing; health expenditure; health inequality; social security system; retirement age